دور رأس المال البشري والأداء المؤسسي في تحقيق الميزة التنافسية في جامعة صحار بسلطنة عمان - شافعي، يوسف سعيد محمد (Kulliyah of Education, International Islamic University Malaysia, 2021)
This study explored the reality of human capital and organizational performance in Achieving Competitive Advantage at Sohar University in the Sultanate of Oman. To this end, the study utilized a descriptive analytical approach, where using a questionnaire was the tool of data collection. The sample to which the study was applied included 208 of administrators and academic faculty for the academic year 2019/2020. Statistical analyses including descriptive analyses (percentages, means, modes, and standard deviations) and Cronbach's Alpha were calculated using SPSS program. The results showed that the level of human capital and institutional performance at Suhar University was average, whereas the level of competitive performance was high. This indicates that the university follows traditional models in human resources management despite its endeavor to apply the best global practices to achieve a distinguished position that makes it competitive in the labor market. The study also concluded that the levels of human capital competencies, commitment of employees to positive behaviors, and employees' awareness at Suhar University were high. Additionally, the study revealed that there was a statistically significant effect of the human capital in achieving competitiveness through the organizational performance of workers at Suhar University. In light of these results, Suhar University was recommended first to take advantage of knowledge progress and technical development to renew the conceptual framework for the standards of the General Authority of Academic Accreditation. Second, the university should use modern methods and means to develop human resources based on the standards of the Omani General Authority for Academic Accreditation.